The Effect of Zinc Supplementation on The Duration of Acute Watery Diarrhea in Children Age 6 Months To 5 Years Old - Jahan, Asma; Mir, Huma; Mohammad, Jan; Jahan, Fatima (Indus Journal of Bioscience Research, 2025)
Introduction: Health burden of acute watery diarrhea in children aged 6 months to 5 years is quite significant. Zinc supplementation could potentially be an effective, affordable intervention which is seldomly investigated locally. Hence the study was planned with aim to explore the potential impact of oral zinc supplementation on the duration of acute watery diarrhea in children aged 6 months to 5 years. Results of the study could benefit clinicians in providing better treatment plan and improve the outcomes in acute diarrheal illness in children. Materials and methods: This randomized controlled trial was carried out at the department of Pediatrics, Khyber Teaching Hospital,during the period from 5th August, 2024 to 5th February,2025. A total of 212 (106 in each group) patients irreaspectve of gender, aged 6 months to5 years presenting with acute diarrhoeal illness were assigned to group A (with zinc supplementation) and B (without zinc supplementation). Efficacy (time to acute diarrhea resolution) was compared in both groups. Results: The mean age of the participants in group A (with zinc) was 2.69±1.19 years compared to 2.75±1.21 years in group B (without zinc). Male participants were 64 (60.4%) in group A while 56 (52.8%) in group B. 64 patients (60.4%) patients reported passing loose stools in group A compared to 50 (47.2%) in group B. 36 patients (34.0%) were breast fed in group A compared to 40 (37.7%) in group B. The mean time to resolution of diarrhea (efficacy) in group A (with zinc) was 3.34±1.27 days and 4.74±1.56 days in group B (without zinc). The p value for mean difference in efficacy was 0.000. Conclusion: Mean time to resolution of diarrhea was significantly lower in patients receiving zinc compared to patients who did not receive it showing the potential beneficial role of zinc in acute diarrheal illness in children.